Fetal loss following second trimester amniocentesis. Who is at greater risk? How to counsel pregnant women?. (16th February 2016) - Theodora, Marianna; Antsaklis, Aris; Antsaklis, Panos; Blanas, Konstantinos; Daskalakis, Georgios; Sindos, Michael; Mesogitis, Spiros; Papantoniou, Nikolaos
Abstract: Objective : The purpose of this retrospective observational cohort study was to determine the impact of certain risk factors on fetal loss, after mid-trimester amniocentesis. Material and methods : Six thousand seven-hundred and fifty-two (6752) consecutive amniocenteses with known pregnancy outcome performed during a 7-year period (2004–2010) were included in this study. Different maternal-, fetal- and procedure-related factors were evaluated in this study. Results : During this 7-year period, 6752 cases who underwent amniocentesis, with complete data available were evaluated for the outcome and risk factors mentioned. Total fetal loss rate (FLR) up to the 24th week was 1.19%. Risk factors associated with increased risk of fetal loss after amniocentesis were maternal age (OR:2.0), vaginal spotting (OR:2.2) and serious bleeding (OR:3.5) during pregnancy, history of 2nd trimester termination of pregnancy (OR:4.0), history of more than three spontaneous (OR:3.0) or surgical first trimester abortions (OR:2.1), fibromas (OR:3.0) and stained amniotic fluid (OR:6.1). Conclusions : Amniocentesis is a safe-invasive procedure for prenatal diagnosis with total FLR of 1.19% in our institution during the study period. The present study has emphasized the significance of certain risk factors for adverse outcome and therefore the need to individualize the risk.